The Expression of the miR-25/93/106b Family of Micro-RNAs in the Adipose Tissue of Women With Polycystic Ovary Syndrome - Wu, Hsiao-Li (J Clin Endocrinol Metab, 2014)
CONTEXT: In adipose tissue (AT) micro-RNA-93 (miR-93) is significantly overexpressed in polycystic ovary syndrome (PCOS) women and non-PCOS women with insulin resistance (IR). Overexpressed miR-93 directly inhibits glucose transporter isoform 4, impairing both glucose metabolism and insulin sensitivity. The mechanisms behind increased miR-93 expression are unclear. OBJECTIVE: Our objective was to determine whether miR-93 expression is concordant with its host gene, MCM7, which contains the miR-25/93/106b gene cluster. PATIENTS: AT was excised from 16 women with PCOS (eight with and eight without IR) and 15 non-PCOS (nine with and six without IR). MAIN OUTCOME MEASURES: Expression of MCM7 and miR-25/93/106b was measured in AT and 3T3-L1 cells. RESULTS: MCM7 expression was lower in both non-PCOS/IR and PCOS women and tended to be lowest in women with PCOS and IR. Overall, the expression of MCM7 in human AT was negatively associated with miR-93 expression and with increased subject IR. Additionally, miR-25 and miR-106b expression is uncoupled from the MCM7 host gene and are positively correlated with IR, although no PCOS-specific difference was observed. MCM7 expression appears to be negatively correlated with increasing fasting glucose. In 3T3-L1 adipocytes, increasing glucose had no effect on miR-93 or miR-25, although it reduced MCM7 and increased miR-106b expression in a dose-dependent fashion. In turn, in 3T3-L1 adipocytes, increasing insulin had no effect on either MCM7 or miR-25/93/106b expression. CONCLUSIONS: Our data suggest that the expression of MCM7 and miR-93/25 is PCOS and IR related, whereas that of miR-106b is related to IR only. In 3T3-L1 adipocytes, neither hyperglycemia nor hyperinsulinemia altered the expression of miR-93 or miR-25, although increasing glucose levels down-regulated MCM7 and paradoxically increased that of miR-106b expression. The expression of the miR-25/93/106b family may be regulated through mechanisms distinct from its host gene, MCM7. Finally, our studies suggest potential epigenetic mechanisms for both IR and PCOS.